Translation techniques in the video subtitles of Knorr (Royco) advertising “ The flavor of home” - Atika Puspasari (Relawan Jurnal Indonesia, 2022)
Even though nowadays technological developments have contributed a lot to the ease of translation, problems in translation will always be encountered due to differences between the source language and the target language. This article aims at identifying techniques of translations used in a Youtube ad. In analyzing the data, the writer applied a content analysis method with a qualitative approach. The findings show that there are 8 categories of translation techniques namely literal translation, transposition, modulation, amplification, established equivalence, generalization, linguistic compression, and adaptation with modulation as the most common translation technique used.